School Heads’ Leadership Practices in The New Normal, Administrative Disposition, and Readiness of The Public Schools in Laguna - Rycel Bungay Villar; Alberto D. Yazon; Consorcia S. Tan; Lerma P. Buenvinida; Marcial M. Bandoy (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
School heads from the Philippines and around the globe are currently affronted by unexpected levels of adversities. They are facing threats, and which have been perennial to many, if not all, school organizations. This study assessed the relationship between the school heads' leadership practices, administrative disposition, and readiness of the public schools among school principals in the City Schools Divisions in Laguna for the school year 2020-2021. Two hundred five (205) public school principals were the respondents of the study. The researcher utilized the descriptive-correlational research design and self-made questionnaire to assess and measure the variables under study. The statistical tools used to analyze the data gathered were Mean, standard deviation, Pearson r and Multiple Linear Regression Analysis. Findings revealed that the school heads' leadership practices and the administrative disposition were highly practiced during the new normal in the education system. In terms of the readiness of the public schools, the results revealed that the schools are much ready. The school heads' leadership practices and administrative disposition related the readiness of the school. The school heads' leadership practices in terms of resiliency in stress management and the administrative disposition in terms of inclusivity and accommodative significantly predicted the readiness of the public schools in the five City Schools Divisions in Laguna. This research contributed to the school’s governance operations and contingency plan that will be used by the five city schools in the division of Laguna.